Biogeographical transitions in the Sierra Madre Oriental, Mexico, shown by chorological and evolutionary biogeographical affinities of passerine birds (Aves: Passeriformes). (24th April 2017) - Ferro, Ignacio; Navarro‐Sigüenza, Adolfo G.; Morrone, Juan J.
Abstract: Aim: To locate areas of biogeographical transitions within the Sierra Madre Oriental (SMO), Mexican transition zone. Location: Eastern Mexico (18° to 27° N – 90° to 96° W) and the Americas. Methods: We deconstructed passerine fauna into biogeographical affinities to map their integration in the studied area. We defined and quantified two features of biogeographical affinity based on raw distributional range concordance (chorological affinity), and on ancestral state reconstruction of published phylogenies (evolutionary biogeographical affinity). Then, we divided the SMO into 500 m elevation intervals and 1.2° latitudinal belts. Point records of resident passerine birds were used to compute species turnover and to map the dominance and heterogeneity of biogeographical affinities along the gradient. Results: Considering the gradient of biogeographical affinities, we identified the sharpest transition at elevations of c . 1500 m from the southern evergreen cloud forests to the canyons of the middle Pánuco basin ( c . 22° of latitude) and then turning eastwards, following the Pánuco river through the semi‐deciduous lowland forest to the river mouth in the Gulf of Mexico. Main conclusions: Our analysis allowed us to map a gradual pattern of variation based on a quantitative definition of biogeographical affinities. This approach is particularly useful for the analysis of rather small areas where a regional biota cannot be partitioned concomitantly with regionalization procedures. Our findings support previous suggestion of a middle elevation zone of mixture between Neotropical and Nearctic biotas, as shown by their chorotypes and cenocrons, and highlight the Pánuco river as a biogeographical boundary dividing northern and southern assemblages based on bird distributions in north‐eastern Mexico.